The effectiveness of reproductive health education to increase knowledge among adolescents - Fina Setyandari; Faizah Betty Rahayuningsih (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Discussion about sexual and reproductive health issues among teenagers and parents is still shadowed by taboos in some cultures. Ignorance and myths surrounding these issues make teenagers vulnerable to the consequences of inappropriate sexual behavior, which in turn exposes them to risky behavioral problems. The lack of knowledge regarding teaching strategies used to educate teenagers can result in their indifferent attitudes and decreased motivation in receiving educational materials.Purpose: To determine the characteristics, age, gender, participants knowledge levels regarding adolescent reproductive health, and the influence of leaflet and booklet media on the level of adolescent reproductive health knowledge.Method: A quantitative research using a quasi-experimental design with a posttest-only design. The sample consisted of 50 teenagers divided into 2 intervention groups. The media used for education were booklets and leaflets.Results: The analysis results for the booklet group with a mean of 67.48 ± 14.060 and the leaflet group with a mean of 54.20 ± 6.331 yielded a ρ-value of 0.001. Therefore, there is a difference in the impact of health education intervention on the level of reproductive health knowledge among teenagers.Conclusion: Providing education using booklets can be one of the more effective educational strategies.Suggestion: Both adolescent boys and girls are encouraged to properly maintain their reproductive health and participate in every available health education activity to enhance their knowledge and health status.